IMPLEMENTASI PENDIDIKAN AKHLAK DI MASA PANDEMI COVID-19 - Minati Kurnia Putri; Muhammad Muhammad (Prodi PAI STIT Sunan Giri Bima, 2022)
This study describes the role of the youth of Masjid Baiturrahman Desa Sepakek Pringgarata Lombok Tengah in the implementation of character education during the Covid-19 pandemic. This type of research uses descriptive qualitative research. Research data was obtained through observation, interviews, and documentation. Data analysis techniques used in this study are data reduction, data display, and verification. For the validity of the data techniques used, namely, increasing persistence, and triangulation. The results of this study indicate that moral education during the Covid-19 pandemic is realized in a container of activities that are regularly arranged such as weekly, monthly, yearly, and conditional-incidental activities. The youth of the Masjid Baiturrahman Desa Sepakek take a significant role in the prosperity of the mosque, the regeneration of the people, and the development of the youth of the mosque.